Cover Image. (8th December 2019) - Yang, Manqi; Rahimnejad, Samad; Zhang, Chunxiao; Song, Kai; Lu, Kangle; Wang, Ling
Abstract : The cover image is based on the Original Article Histomorphology of gastrointestinal tract in bullfrog Rana (Lithobates) catesbeiana and evaluation of the changes induced by a soybean meal‐based diet by Manqi Yang et al., https://doi.org/10.1111/are.14361 .